Changes in radical levels as a cause for the FLASH effect: impact of beam structure parameters at ultra-high dose rates on oxygen depletion in water - Jansen, Jeannette; Beyreuther, Elke; Garcia-Calderón, Daniel; Karsch, Leonhard; Knoll, Jan; Pawelke, Jörg; Schürer, Michael; Seco, Joao (Radiotherapy and oncology, 2022)
The influence of different average and bunch dose rates in electron beams on the FLASH effect was investigated. The present study measures O2 content in water at different beam pulse patterns and finds strong correlation with biological data, strengthening the hypothesis of radical-related mechanisms as a reason for the FLASH effect.